Localization vs. standardization: Global approaches to CSR management in multinational companies - Silke Bustamante (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2011)
The present paper identifies and structures external and internal influences on CSR Management of global companies. It suggests consequences for localization of different levels of CSR Management in the light of influencing factors such as stakeholder power, organizational culture and issues in question. In order to set the framework, general management approaches of global companies as a response to integration and responsiveness pressures and the most important dimensions of CSR management will be revised. In a second step, external and internal pressures on integration and localization strategies will be described and structured, leading to the identifications of three major aspects influencing CSR management of companies: Issues, key stakeholders, and strategic/organizational considerations. Based on this, possibilities of companies to localize their CSR approach within the different management dimensions and in the light the major forces on CSR management will be proposed. – – Das Working Paper identifiziert und strukturiert externe und interne Einfußfaktoren auf das CSR Management globaler Unternehmen und zeigt in Abhängigkeit wesentlicher Faktoren wie Schlüsselstakeholder, Organisationskultur und CSR Themen Möglichkeiten der Anpassung unterschiedlicher Dimensionen des CSR Managements auf. In einem ersten Schritt werden grundsätzliche Strategien globaler Unternehmen als Antwort auf Integrations- bzw. Adaptationserfordernisse sowie die wichtigsten Dimensionen des CSR Managements dargestellt. Darauf aufbauend werden externe und interne Einflussfaktoren auf Integrations- bzw. Lokalisierungsstrategien beschreiben und strukturiert und die wichtigsten Einflussfaktoren des CSR Managements identifiziert: CSR Themen (Issues), Schlüsselstakeholder sowie strategische und organisatorische Erwägungen. Schließlich werden Möglichkeiten der Lokalisierung des CSR Managements in den unterschiedlichen Management Dimensionen und vor dem Hintergrund der drei Einflussfaktoren vorgeschlagen.
Keywords: 650